2022
DOI: 10.1097/j.jcrs.0000000000001027
|View full text |Cite
|
Sign up to set email alerts
|

Comparative visual outcomes of EDOF intraocular lens with FLACS vs conventional phacoemulsification

Abstract: To investigate the visual quality after femtosecond laser-assisted cataract surgery (FLACS) and conventional phacoemulsification surgery (CPS) with the implantation of an extended depth-of-focus (EDOF) intraocular lens (IOL) TECNIS Symfony.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Filkorn et al 31 suggested that FLACS might enhance the predictability of IOL power calculation compared with conventional cataract surgery, particularly in short (axial length <22.0 mm) and long (axial length >26.0 mm) eyes. FLACS has also been reported to reduce optical aberrations and improve optical quality and patient satisfaction 32–34 . Several studies have reported that FLACS showed better visual outcomes than conventional cataract surgery, particularly in cases with implantation of an extended-depth-of-focus IOL 16,34,35 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Filkorn et al 31 suggested that FLACS might enhance the predictability of IOL power calculation compared with conventional cataract surgery, particularly in short (axial length <22.0 mm) and long (axial length >26.0 mm) eyes. FLACS has also been reported to reduce optical aberrations and improve optical quality and patient satisfaction 32–34 . Several studies have reported that FLACS showed better visual outcomes than conventional cataract surgery, particularly in cases with implantation of an extended-depth-of-focus IOL 16,34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…FLACS has also been reported to reduce optical aberrations and improve optical quality and patient satisfaction 32–34 . Several studies have reported that FLACS showed better visual outcomes than conventional cataract surgery, particularly in cases with implantation of an extended-depth-of-focus IOL 16,34,35 . However, other studies failed to demonstrate any significant difference in visual and refractive outcomes between FLACS and conventional cataract surgery 5,36–39 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex optical design of the EDOF IOL showed higher sensitivity to IOL tilt and decentration, which might lead to larger HOAs, diminishing the effect and satisfaction of EDOF IOL implantation [ 23 , 24 ]. FLACS has been reported to achieve unparalleled accuracy and precision in the size, shape, and position of capsulorhexis, resulting in higher refractive predictability, less corneal edema, and less IOL tilt or decentration [ 5 , 6 , 7 , 8 ]. To our knowledge, no previous study has comprehensively compared the clinical outcomes between FLACS and CPS with the implantation of an EDOF IOL.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the clinical application of the femtosecond laser has led to new developments for cataract surgery. Combined with computer-controlled optical delivery systems, this technique has the advantages of more precise circularity and adjustability of the capsulorhexis diameter, nucleus fragmentation of lenses, arcuate keratotomy, and multi-plane self-sealing incision creation without collateral damage to surrounding tissues [ 5 , 6 , 7 , 8 ]. A more precise capsulotomy prior to the implantation of aspheric or multifocal IOLs contributes to better visual results, as the tilt or decentration of the IOL can led to higher asymmetrical aberrations [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%